Metacognitive Awareness and Self-Efficacy: A Closer Look at the Profiles of Arabic Learners at an Islamic University in Indonesia - Sholihah, Diana Nur (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
While numerous studies have established the roles of metacognitive awareness and self-efficacy in foreign and second language teaching and learning, research specifically focusing on Arabic language acquisition in this context remains limited. This study aims to examine the metacognitive awareness and self-efficacy of Arabic language learners at Universitas Islam Tribakti Lirboyo Kediri. The participants in this study consisted of 72 Arabic learners. To collect data, two types of instruments were used: the Junior Metacognitive Inventory and the Self-Efficacy Questionnaire for Language Learning Strategies. The collected data were analyzed statistically by calculating the percentages of students based on their levels of metacognitive awareness and self-efficacy. The Kolmogorov-Smirnov test was employed to assess the normality of the data, while the Levene test was used to check for homogeneity. A t-test was conducted to analyze the significance of the differences in metacognitive awareness and self-efficacy between male and female learners. The results indicated that the metacognitive awareness of the Arabic learners varied across different levels, both in terms of cognitive knowledge (very good, good, fair, poor) and in the regulation of cognition (very good, good, fair). There was a significant difference between male and female learners in the regulation of cognition, while no significant difference was found regarding knowledge of cognition. Additionally, the Arabic learners exhibited varying levels of self-efficacy, including competence, confidence, and comfort; however, the difference between male and female learners in this area was not significant.